Impact of HIV-1 co-infection on tuberculosis and value of CD4+ lymphocyte counts and concurrent antigen testing in interpretation of tuberculin reactions in hospitalized children with tuberculosis in South Africa - Madhi, Shabir Ahmed (My University, 2014)
There are few reports on the impact of HIV-1 infection on tuberculosis in children. Microbiologic diagnosis of tuberculosis is difficult and much reliance is placed on the tuberculin skin test, as part of a scoring system, in diagnosing tuberculosis in children. A prospective study, enrolling 168 patients with clinical tuberculosis, was performed between July 1996 and January 1997 at the teaching hospitals attached to the Department of Paediatrics and Child Health, University of the Witwatersrand. Forty-two percent of children with tuberculosis were HIV-1 infected. Extrapulmonary tuberculosis was diagnosed more frequently in HIV uninfected children. Progressive pulmonary tuberculosis, based on radiographic findings, and mortality was higher in HIV-1 infected children with tuberculosis. HIV-1 infected children with pulmonary tuberculosis showed marked hyporeactivity to tuberculin skin testing. Both CD4+ lymphocyte counts and concurrent delayed type hypersensitivity testing, using the "CMI Multitest®”, offered little value in interpreting the tuberculin skin test in HIV-1 infected children with tuberculosis. The findings of the study suggest that aggressive microbiologic investigations coupled with a low threshold of clinical suspicion is essential in diagnosing tuberculosis in children, especially in HIV infected children.
Keywords: Tuberculosis--in infancy & childhood; HIV Infections--in infancy & childhood; Tuberculin Test